Genomic and phenotypic insights into the first imported monkeypox virus clade Ia isolate in China, 2025 - Yin, Chunhong; Li, Yan; Duan, Qing; Xu, Dali; Li, Chengyunxiao; Liu, Ti; Ding, Shujun; Zhang, Zhe; Zhang, Aihua; Fu, Lianchen; Kou, Zengqiang (Frontiers in Public Health, 2025)
The 2022 multi-country outbreak of monkeypox virus (MPXV) sparked global health concerns, as cases emerged increasingly outside traditionally endemic regions. This outbreak, spanning 2022–2023, was primarily driven by the clade IIb strain. Subsequently, a surge of MPXV cases caused by clades Ia and Ib in the Democratic Republic of the Congo and other African countries has garnered heightened attention. Notably, clade Ib has recently been imported into China. In this study, we report the first identification and genetic characterization of a novel imported MPXV strain in China, from a patient returning from an endemic area. Whole-genome sequencing and phylogenetic analysis confirmed its close relationship to MPXV clade Ia, which has not been previously reported in China. The strain was successfully isolated using Vero-E6 cell inoculation. Compared with the reference MPXV clade I strain, the imported Ia strain exhibited substantial genomic divergence, with 67 mutations identified. Among them, 28 non-synonymous mutations were found in genes associated with host interaction and viral pathogenesis. This study highlights the critical role of genomic surveillance and rapid molecular diagnostics in monitoring MPXV transmission and evolution. The successful isolation of a clade Ia strain provides a valuable resource for future research on its pathogenicity and for the development of targeted therapeutics.